2016
DOI: 10.16986/huje.2016016672
|View full text |Cite
|
Sign up to set email alerts
|

Lise Koridor Duvarlarında Kullanılan Renklerin Öğrencilerin Algısal Değerlendirmeleri Üzerindeki Etkileri

Abstract: ÖZ: Bu araştırmada, okul koridorlarının iç mekânında kullanılan farklı renklerin (krem, mavi ve yeşil) öğrencilerin algısal performansı üzerindeki etkilerinin belirlenmesi amaçlanmıştır. Bu maksatla, Ankara'da bulunan İncirli Teknik ve Endüstri Meslek Lisesi koridorları araştırma ortamı olarak seçilmiştir. Öğrencilerin üç farklı renge sahip koridorları 11 sıfat çiftinden oluşan anlamsal farklılaşma ölçeği ile değerlendirmeleri sağlanmıştır. Elde edilen veriler istatistiksel olarak değerlendirilmiş ve önemli so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Furthermore, females reported that they found blue and green colors to be more peaceful and calming compared to males. In a study by Çağatay et al [31] it was reported that female university students preferred pink and orange colors on the walls of rooms, whereas males preferred blue and white colors. The studies treated above showed that there were significant differences between genders in spatial color perceptions.…”
Section: H1cmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, females reported that they found blue and green colors to be more peaceful and calming compared to males. In a study by Çağatay et al [31] it was reported that female university students preferred pink and orange colors on the walls of rooms, whereas males preferred blue and white colors. The studies treated above showed that there were significant differences between genders in spatial color perceptions.…”
Section: H1cmentioning
confidence: 99%
“…A pre-questionnaire was conducted for determining the colors and the usage rates that would be used on the walls of the experimental spaces. Warm, cool, and neutral colors were used, which were used previously in the studies made by Hidayetoğlu et al [22], Yıldırım et al [12,33], Çağatay et al [31], and Müezzinoğlu et al [16], in the determination of the colors included in the pre-questionnaire. It was requested from the participants that they select "the warmest, the coolest, and the most neutral" colors of the 20 colors found in the questionnaire.…”
Section: Selection Of Colorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Yildirim, Cagatay & Ayalp (2015), it was claimed that blue classrooms were perceived more positively compared to cream and pink classrooms by male students and furthermore, classrooms with different colors were evaluated by being perceived as more positive by students. In the study by Cagatay, Hidayetoglu & Yildirim (2017) of school corridors in which different colors were used, it was stated that the cream-colored corridors were perceived more positively compared to blue-and green-colored corridors. In the doctorate dissertation by Muezzinoglu (2018), it examined the effects on the perceptual evaluations of test specimens for three different colors (warm, neutral, cool) used in educational spaces according to the spatial quality, social adaptation and individual productivity scales.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…The use of color in the educational spaces and the contribution provided to education are an important field of study. The studies that research the effects of color on physiological and psychological perception show that the color of the environment is effective on the creativity of the user, the emotional mental status, motivation, concentration and performance, environmental communication and behaviors (Cagatay, Hidayetoglu, & Yildirim, 2017;Engelbrecht, 2003;Hathaway, 1987;M.L. Hidayetoglu, 2010;Muezzinoglu, 2018;Stone, 2003;Stone & English, 1998;Wang & Russ, 2008;K.…”
Section: Introductionmentioning
confidence: 99%